Letter from Campbell Morfit to Richard Sears McCulloh, November 28, 1850 - Morfit, Campbell (1850)
Campbell Morfit (1820-1897), a distinguished chemist and co-editor with James Curtis Booth (1810-1888) of the Encyclopedia of Chemistry (1850), writes to Richard Sears McCulloh (1818-1894) regarding his method for refining of gold and suggests that he sell it to the U.S. Government.
Keywords: Booth, James Curtis, 1810-1888; Morfit, Campbell, 1820-1897; Chemists; Metals--Refining; McCulloh, R. S. (Richard Sears), 1818-1894; Gold--Refining; United States Mint; Mint of the United States